2017
DOI: 10.1016/j.cortex.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Pure word deafness following left temporal damage: Behavioral and neuroanatomical evidence from a new case

Abstract: Pure Word Deafness (PWD) is a rare disorder, characterized by selective loss of speech input processing. Its most common cause is temporal damage to the primary auditory cortex of both hemispheres, but it has been reported also following unilateral lesions. In unilateral cases, PWD has been attributed to the disconnection of Wernicke's area from both right and left primary auditory cortex. Here we report behavioral and neuroimaging evidence from a new case of left unilateral PWD with both cortical and white ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…The end result of the second block is a set of identified (whether correctly or incorrectly) speech sounds. Having a block dedicated to the identification of speech sounds is consistent with certain cortical lesions that adversely affect the recognition of speech sounds, but not any other sounds ( Maffei et al 2017 ).…”
Section: Model Of Speech Understandingmentioning
confidence: 98%
“…The end result of the second block is a set of identified (whether correctly or incorrectly) speech sounds. Having a block dedicated to the identification of speech sounds is consistent with certain cortical lesions that adversely affect the recognition of speech sounds, but not any other sounds ( Maffei et al 2017 ).…”
Section: Model Of Speech Understandingmentioning
confidence: 98%
“…In addition to variability across studies, low reproducibility across subjects is also reported. Some groups have been able to reconstruct AR tracts on both hemispheres on 100% of subjects (Behrens et al, 2007; Profant et al, 2014; Maffei et al, 2017). In contrast, even when using similar diffusion models (e.g., ball-and-stick), other studies report reconstructions successful in both hemispheres in much lower proportions, such as 35–50% (Crippa et al, 2010) or 71–86% (Javad et al, 2014).…”
Section: The Acoustic Radiation In Primatesmentioning
confidence: 99%
“…Damage to the auditory regions, most often the result of brain infarct or traumatic injury, has been associated generally with rare auditory syndromes, such as verbal auditory agnosia (Shivashankar et al, 2001), environmental auditory agnosia (Taniwaki et al, 2000), and cerebral (or central) deafness (Griffiths, 2002). However, until now, only one study investigated the extent of WM damage to the AR in a patient suffering from verbal auditory agnosia (Maffei et al, 2017). Investigating the extent of damage to the AR in patients suffering speech-related comprehension deficits would potentially enhance our understanding of the involvement of the AR in language processing.…”
Section: The Acoustic Radiation: Functional and Clinical Implicationsmentioning
confidence: 99%
“…The medial geniculate bodies have also been known to facilitate the efficient transmission of auditory linguistic signals in speech to preserve and perceive environmental sounds ( 175 ). Pathology associated with the medial geniculate body is generalized auditory agnosia and a reduced ability to understand auditory inputs ( 171 , 176 ). Partially because of the close connection between the medial geniculate bodies and other subcortical structures such as the hippocampus and amygdala, a rodent model traumatic brain injury study found abnormally increased activity in the medial geniculate bodies in connection to auditory-induced post-traumatic stress and amygdala dysfunction ( 177 ).…”
Section: Regional Brain Anatomy and Associated Post-concussion Symptomsmentioning
confidence: 99%
“…Studies have shown that damage to acoustic radiation is associated with hearing and language disorders, auditory processing deficits, and decreased speech comprehension ( 174 ). More serious damage could lead to cortical (central) deafness ( 117 , 149 ), environmental sound agnosia, total auditory agnosia of all sounds ( 149 ), or verbal deafness (word agnosia) ( 175 , 176 ). Additionally, an individual can experience auditory hallucinations (i.e., the experience of hearing music in the absence of any external stimuli) ( 150 ) or tinnitus ( 234 ).…”
Section: Regional Brain Anatomy and Associated Post-concussion Symptomsmentioning
confidence: 99%